INVESTIGATION OF THE GEOMETRIC AND KINEMATIC PARAMETERS OF THE EXCAVATOR, TAKING INTO ACCOUNT THE ENERGY SPENT ON DIGGING THE SOIL - Aliev Nomoz; Abdurazzokov Umidulla (Journal of new century innovations, 2023)
Abstract. In this article have discussed geometric and kinematic parameters of the excavator, taking into account the energy spent on digging the soil.